Bifidobacterium animalis subsp. lactis HN019 live probiotics and postbiotics: production strategies and bioactivity evaluation for potential therapeutic properties - D’ambrosio, Sergio; Dabous, Azza; Sadiq, Saba; Casillo, Angela; Schiraldi, Chiara; Cassese, Elisabetta; Bedini, Emiliano; Corsaro, Maria Michela; Cimini, Donatella (Frontiers in Bioengineering and Biotechnology, 2024)
B. animalis subsp. lactis HN019 is a commercially available well-characterized probiotic with documented effects on human health, such as the ability to enhance the immune function and to balance the intestinal microbiome. Therefore, optimizing the manufacturing process to improve sustainability, increasing biomass yields and viability, and avoiding animal -derived nutrients in the medium to meet vegan consumer's needs, is currently of interest. Besides the established use of live probiotic cells, and due to fewer technological limitations, such as easier production processes and scale-up, and even higher specificity, alternative supplements indicated as postbiotics, like non-viable cells and/or probiotics derived bioactive molecules might be considered as potential next generation biotherapeutics. In this work, medium design together with different fermentation strategies (batch, fed-batch and in situ product removal) on lab-scale bioreactors were combined to increase the titer of viable B. lactis HN019 up to 2.9±0.1x10 10 and to study the physiology of this strain. On the other hand, the EPS isolated from the fermentation broth was characterized and tested, for the first time up to date, in in vitro biological assays, in comparison to live cells and whole heat inactivated broth. Interestingly, EPS and live cells samples demonstrated immune-stimulating properties by downregulating the expression of TLR-4 and NF-KB in LPS challenged differentiated CaCo-2 cells, and the ability to promote restoring the integrity of the intestinal barrier by up-regulating the expression of zonulin, one of the tight junctions forming proteins. Postbiotics in the form of heat killed broth only reduced NF-KB expression, whereas they did not seem effective in the other tested conditions.